KINERJA PENYULUH PERTANIAN LAPANGAN TANAMAN PANGAN DI WILAYAH KERJA UPT KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Shandy Andika; Begem Viantimala; Indah Nurmayasari (Lampung University, 2019)
The purposes of this study are to analyze level of Agricultural Extension Workers (AEWs)’s performance in Technical Implementation and factors related to the level of the performance in working area of Jati Agung Subdistrict of Lampung Selatan District,. This research was conducted in Jati Agung Subdistrict of Lampung Selatan District in September-October 2017. Respondents were 76 randomly selected rice farmers in the area. Data analysis uses descriptive analysis and Rank Spearman correlation test. The results indicated that the level of performance of AEWs in Technical Implementation is included ina medium category. Reward system is significantly related to the level of AEWs’ performance, while motivation level, income level, education level, number of farmers, and distance of residency are not significantly related to the level of AEWs’ performance in Technical Implementation Unit Jati Agung Subdistrict.Key words: AEW, performance, Technical implementation unit